IL-21 Optimizes the CAR-T Cell Preparation Through Improving Lentivirus Mediated Transfection Efficiency of T Cells and Enhancing CAR-T Cell Cytotoxic Activities - Du, Li; Nai, Yaru; Shen, Meiying; Li, Tingting; Huang, Jingjing; Han, Xiaojian; Wang, Wang; Pang, Da; Jin, Aishun (Frontiers in Molecular Biosciences, 2021)
Adoptive immunotherapy using CAR-T cells is a promising curative treatment strategy for haematological malignancies. Current manufacture of clinical-grade CAR-T cells based on lentiviral/retrovirus transduction of T cells followed by anti-CD3/CD28 activation supplemented with IL-2 has been associated with low transfection efficiency and usually based on the use of terminally differentiated effector T cells. Thus, improving the quality and the quantity of CAR-T cells are essential for optimizing the CAR-T cell preparation. In our study, we focus on the role of IL-21 in the γc cytokine conditions for CAR-T cell preparation. We found for the first time that the addition of IL-21 in the CAR-T preparation improved T cell transfection efficiency through the reduction of IFN-γ expression 24h to 48h after T cell activation. We also confirmed that IL-21 enhanced the enrichment and expansion of less differentiated CAR-T cells. Finally, we validated that IL-21 improved the CAR-T cell cytotoxicity, which was related to increased secretion of effector cytokines. Together, these findings can be used to optimize the CAR-T cell preparation.